2012
DOI: 10.1103/physrevb.86.224408
|View full text |Cite
|
Sign up to set email alerts
|

Sign of the superexchange coupling between next-nearest neighbors in EuO

Abstract: The sign of the superexchange coupling J 2 between next nearest neighboring Eu 2+ magnetic moments in EuO is a matter subject to debate. We have obtained evidence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…Prior studies reported an increase in Curie temperature for EuO with electron doping (n-type doping of the EuO). 12,29 As seen in Figure 2, there is no significant change in the critical magnetization temperature neither for LSMO (Ref. 23) nor for EuO with polarization reversal in BTO.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…Prior studies reported an increase in Curie temperature for EuO with electron doping (n-type doping of the EuO). 12,29 As seen in Figure 2, there is no significant change in the critical magnetization temperature neither for LSMO (Ref. 23) nor for EuO with polarization reversal in BTO.…”
mentioning
confidence: 74%
“…The magnetic properties were measured with a physical properties measurement system (PPMS) from Quantum Design. 12,15,29 As seen in Figure 1, the 100-nm-thick EuO films are textured along (100). The results obtained for the EuO/BaTiO 3 samples are here compared with the data obtained previously using epitaxial BaTiO 3 films on La 0.67 Sr 0.33 MnO 3 /SrTiO 3 (LSMO/STO) substrates.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The element and orbital selectivity of core level resonant spectroscopies allows to access higher order multipoles which are left unexplored by MCD in X-ray absorption (XAS) [1][2][3][4][5][6], to distinguish and enhance specific electronic excitations and satellites [7,8], collective magnetic excitations [9], ultrafast and charge transfer dynamics [10][11][12] and to detect quadrupolar transitions towards localized empty states [13,14]. In particular, RPES has recently been applied to several correlated materials [15][16][17][18][19] and full two dimensional angular scans of resonantly emitted electrons in moderately correlated materials have also been carried out [20,21]. These works, together with earlier pioneering studies [22,23] on local magnetic properties in macroscopically non magnetic systems, demonstrate the importance of RPES and the need for an advancement in the theoretical description of this spectroscopy, which is the main aim of this work.…”
mentioning
confidence: 99%